Risks and foreign direct investment inflows: Evidence from Yemen - Al-Jaifi, Hamdan Amer Ali; Abdullah, Nur Adiana Hiau; Regupathi, Angappan (Universiti Kebangsaan Malaysia, 2016)
This study aims to find the relationship between the political, exchange rate and inflation risk factors with the Yearly Foreign Direct Investment (YFDI) in Yemen, over the period between 1990 to 2010. Secondary data results showed that political risk and exchange rate risk have an inverse relationship with YFDI, while inflation risk has a significant positive relationship.Further analysis on a survey collected from 62 multinational enterprises (MNEs) operating in Yemen showed an insignificant relationship between the perceived political, exchange rate and inflation risk factors and corporate foreign direct investment (CFDI).The conflicting results possibly imply that the MNEs' subsequent capital investments may not be affected by the perceived political, exchange rate and inflation risks that would nonetheless have been considered during the initial business plan.It is likely that MNEs that were already operating in Yemen may have developed capabilities in terms of knowledge, bargaining and lobbying skills.Therefore, perceived risks are no longer seem to influence their investment decisions.